AN ANALYSIS ON STUDENTSâ MASTERY IN USING GERUND AT THE FIFTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM IN UNIVERSITY OF PASIR PENGARAIAN - Nasution, Andri Winata; Rahayu, Pipit; Antoni, Rivi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research was aimed to find out and analyze the skill of the fifth semester students of English study Program in University of Pasir Pengaraian in using gerund. In collecting the data, the researcher conducted 2 sessions of the test, they were try out test and post test where the purpose of the try out test is to determine the validity of the test items given to the students. The method used in this research was descriptive qualitative research.There were several types of gerund used in this research. Overall, based on the result of this research, the whole test result which was done by students explain that from the 30 multiple chice test items given the percentage of the correct answer from the all respondents was 50 %. It means that their skill in using gerund can be categorized in the poor level (weak).